Identifying predictive motor factors for falls in post-menopausal breast cancer survivors. - Marek Zak; Malgorzata Biskup; Pawel Macek; Halina Krol; Szymon Krupnik; Anna Opuchlik (PLoS ONE, 2017)
OBJECTIVE:Breast cancer treatment, including radical surgery, is also pursued as late as the 7th - 8th decade of women's lives. Standard physical rehabilitation procedures offered to those women are predominantly focused on attenuating specific functional deficits of the upper limb and trunk. Seldom do they entail any regimens specifically aimed at recovering overall functionality, and reducing exposure to falls-risk. The study aimed to assess potential interrelationships between the self-reported falls, individual functional capabilities and appreciably reducing exposure to falls-risk in a group of post-menopausal, post-surgical breast cancer survivors. METHODS:The study recruited 102 women (aged 65-79; mean age 70.2), post-surgical breast cancer survivors. The subjects were stratified by age into three groups: Group 1 (65-69 years); Group 2 (70-74 years), and Group 3 (75-79 years). Individual functional capabilities were assessed with Eight-foot up & go test (8UG), chair stand test (CST), and 2-minute step test (2ST). Tinetti POMA test was applied to assess gait and balance disorders. Self-reported falls in the past year were ascertained through a questionnaire. RESULTS:Assessment of individual aerobic endurance (2ST) also demonstrated a clear deficit in the mean scores category in all respective age sub-groups, as compared against the reference values. The deficits ranged from 4.86 to 15.90 steps less than the normative values; the oldest subjects demonstrating the largest deficit. The aerobic endurance tests results significantly impacted the ultimate assessment of an individual falls-risk in the oldest group. The analysis of the number of falls sustained within the recent year indicated that 43.67% of the subjects fell victim of such incidents. CONCLUSION:An individual exposure to falls-risk was found to be appreciably more dependent upon individual aerobic endurance rather than overall strength of the lower part of the body in the breast cancer survivors over 75.